1998
DOI: 10.1046/j.1472-765x.1998.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Saccharomyces strains in wine fermentations: analysis for two consecutive years

Abstract: An ecological study of Saccharomyces cerevisiae strains in spontaneous alcoholic fermentation has been conducted in the same winery for two consecutive years (1994 and 1995). Yeast cells were identified and characterized using mitochondrial DNA restriction analysis. Although a great diversity of wild strains was observed, a sequential substitution of S. cerevisiae strains during the different phases of fermentation was detected. Furthermore, the most frequent strains were encountered in both years, and the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
58
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 11 publications
24
58
0
3
Order By: Relevance
“…In some cases, only one or a few strains dominate throughout fermentation (Versavaud et al 1995). In contrast, other researchers have found that different strains dominate at different stages of the fermentation (Egli et al 1998, Sabate et al 1998, Schütz and Gafner 1993 or that several strains of Saccharomyces appear to be simultaneously present in equivalently high numbers (Torija et al 2001. Presumably, the biodiversity of wine strains in the environment results in these different patterns of dominance in fermentations.…”
Section: Functional Diversity Of Wine Strainsmentioning
confidence: 92%
See 1 more Smart Citation
“…In some cases, only one or a few strains dominate throughout fermentation (Versavaud et al 1995). In contrast, other researchers have found that different strains dominate at different stages of the fermentation (Egli et al 1998, Sabate et al 1998, Schütz and Gafner 1993 or that several strains of Saccharomyces appear to be simultaneously present in equivalently high numbers (Torija et al 2001. Presumably, the biodiversity of wine strains in the environment results in these different patterns of dominance in fermentations.…”
Section: Functional Diversity Of Wine Strainsmentioning
confidence: 92%
“…Significant genetic diversity exists among wine strains of S. cerevisiae whether isolated from the vineyard or winery (Baleiras Couto et al 1996, Briones et al 1996, Gallego et al 2005, Khan et al 2000, Lopes et al 2002, Sabate et al 1998, Schütz and Gafner 1993, Valero et al 2006, Van der Westhuizen et al 2000a, 2000b, Versavaud et al 1995) and the same is true of S. bayanus (Sipiczki 2002). Analysis of over 1,600 isolates of S. cerevisiae from 54 spontaneous fermentations demonstrated the existence of 297 unique strains .…”
Section: Functional Diversity Of Wine Strainsmentioning
confidence: 99%
“…Improvement of DNA extraction procedure the mtDnA-RFlP analyses have been used by various authors to characterize and differentiate S. cerevisiae industrial strains and have been reported to be successfully used in discrimination among yeast strains isolated from the same must and in monitoring the presence and prevalence of a specific yeast strain during the whole fermentative process (15,16,20,23). Usually, when mtDNA is analyzed, yeasts are recovered from commercially dry form in order to further obtain culture in liquid medium.…”
Section: Resultsmentioning
confidence: 99%
“…[12] report, the conversation of reducing sugar in to ethanol and carbon dioxide is due to the activity of microbes. …”
Section: Effect Of Oxygen On Quality Of Winementioning
confidence: 99%